Chronic neck pain in high school students: characterization and effectiveness of pain neuroscience education and exercise - Andias, Rosa Maria de Sousa (2022)
The prevalence of chronic idiopathic neck pain (NP) in young people is increasing and it is the leading musculoskeletal complaint in adolescents. NP results in limitations of daily living activities and is a risk factor for having NP in adulthood. It has also been reported to be associated with functional and psychosocial factors, disability, impaired sleep, and central sensitization. However, studies characterizing adolescents with NP compared to asymptomatic or to adolescents with other musculoskeletal pain conditions or exploring the factors associated with current and future NP and disability are scarce. There is also a lack of evidence on the effectiveness of physical therapy management of NP in adolescents. Therefore, the two main aims of this research project were i) to characterize NP and associated psychosocial and functional changes, disability, sleep, and self-reported symptoms of central sensitization in adolescents and ii) to assess the effectiveness of Pain Neuroscience Education (PNE) and exercise compared to exercise only for adolescents with NP. This research project consists of two systematic reviews of the literature (Chapters 3 and 4), which reviewed the evidence on the association between functional and psychosocial changes, sleep, and central sensitization and NP in adolescents; three observational studies (Chapters 5, 6, and 7), which explored the factors associated both with NP and disability (Chapter 5), the factors associated with the persistence of chronic NP and disability at 6-month follow-up (Chapter 6) and with the new onset of NP at 6- month follow-up in adolescents (Chapter 7); and one randomized controlled trial (Chapter 8) which assessed the effectiveness of PNE and exercise compared to exercise only at post-intervention and at 6-month follow-up in adolescents with NP, at the school setting. Chapters 3 and 4 found very limited to limited evidence suggesting that depression, anxiety and stress, catastrophizing, poor self-efficacy, sleep impairments, deficits in muscle function and proprioception, and low pain thresholds are associated with NP in adolescents. Chapters 5 and 6 highlighted that female sex, psychosocial factors, disability, physical activity, sleep, and self-reported symptoms of central sensitization are associated with chronic NP and disability and its persistence at 6 months, and Chapter 7 further highlighted the association of these factors for the new onset of NP, specifically, sleep and self-reported symptoms of central sensitization. Chapter 8 suggested that exercise and exercise plus PNE were similarly effective in treating adolescents with NP. These findings support the inclusion of psychosocial factors, disability, physical activity, sleep, and self-reported symptoms of central sensitization in the assessment of adolescents with NP, and the need for their preventive assessment in asymptomatic adolescents. Furthermore, it encourages the application of interventions based on exercise and exercise plus PNE for the management of chronic NP in adolescents, at the school setting.